Android 6 app development fundamentals I and II (LiveLessons., 2016)
"Android App Development Fundamentals 3/e uses Paul Deitel's unique 'app-driven' approach to get you up and running quickly with Google's popular Android 6.0 SDK (Marshmellow). Paul Deitel--best-selling author and Oracle Java Champion--carefully introduces you to Android app development with key Android 6.0 features and APIs. You'll first learn how to install and configure Google's Android Studio IDE. Using the Deitel's signature App-Driven Approach in which all concepts are presented in the context of complete working apps, you'll then build seven Android apps that introduce everything you need to start creating your own--Welcome app, Tip Calculator app, Flag Quiz app, Doodlz drawing app, Cannon Game app, WeatherViewer app, Twitter Searches app, and Address Book app. Along the way, you'll learn to master the Android APIs and FrameWorks needed to become a successful Android app developer."--Resource description page.